Frequency speed of kick test performance comparison between female taekwondo athletes of different competitive levels - Santos, J. F. S.; Franchini, E. (The Journal of Strength and Conditioning Research, 2018)
Construct validity is a desirable characteristic in any performance test to differentiate athletes. However, no taekwondo-specific test was investigated with this purpose. The purpose of this study was to compare female taekwondo athletes grouped in different competitive levels. Forty-two female taekwondo athletes divided into International/National (median [interquartile range]; n = 21, age: 20 [18-25] years; body mass: 60 [53-72] kg; height: 164 [161-170] cm; and practice time: 8 [5-13] years) and State/Regional group (median [interquartile range]; n = 21; age: 18 [17-25] years; body mass: 57 [52-63] kg; height: 165 [160-172] cm; and practice time: 5 [2-8] years) volunteered to participate in this study. The female taekwondo athletes performed frequency speed of kick test (FSKT) with 10 seconds (FSKT10s) and intermittent 90 seconds (FSKTmult) during the competitive period. Differences between international/national and state/regional group were observed, with superiority to international/national group, for FSKT10s (U = 114.5, p = 0.007, ESr (effect size) = -0.42 [small]), FSKT1 (U = 127.0, p = 0.016, ESr = -0.37 [small]), FSKT2 (U = 108.5, p = 0.004, ESr = -0.45 [small]), FSKT3 (U = 127.0, p = 0.015, ESr = -0.37 [small]), and FSKTtotal (U = 124.0, p = 0.015, ESr = -0.38 [small]). Based on the results of this study, the FSKT seems to be a good tool to discriminate performance of female taekwondo athletes and could be used by coaches and athletes in their evaluation routines.